Microwave assisted synthesis of some azo disperse dyes part 2: Eco-friendly dyeing of polyester fabrics by using microwave irradiation - Saleh, Mohamed Osman; El-Apasery, Morsy Ahmed; Hussein, Abdelhaleem Mostafa; El-Adasy, Abu-Bakr Abdelhady; Kamel, Magda Mohamed (European Journal of Chemistry, 2021)
This study aimed to use microwave irradiation as a green technique, not only to enhance the dyeing efficiency of disperse-colored polyester fabrics, but also to conserve resources and minimize the environmental effects. Arylazopyrazolopyrimidinones dyes 1-9 were applied to polyester fabrics at 2% shade using conventional method and microwave at 100 °C. Both the color intensity expressed as dye absorption and the fastness characteristics of the dyed fabric were investigated. The K/S values are increased by increasing the time of irradiation from 10-60 minutes. The dyed substrate displayed good light fastness, and very good fastness levels to rubbing, perspiration washing, and sublimation, respectively.